Genetic analysis and correlation in sweet corn (Zea mays) for quali(y traits, field emergence and grain yield* - KUMARI, JYOTI; GADAG, R N; JHA, G K (The Indian Journal of Agricultural Sciences, 2011)
Sweet corn (Zea mays L. var rugosa) is most popular in USA, Canada, Japan and Taiwan. In India, sweet corn is cultivated mainly in Andhra Pradesh, Karnataka and Maharashtra but it is gaining importance in other parts of country as well. Sweet corn is consumed at immature grain stages of endospenn at 20-22 days after fertilization in various forms. Nearly all-commercial sweet corn is based on one or more homozygous recessive alleles (Coe and Polaco 1994) that alter the kernel carbohydrate content. Traditional sweet corn variety is homozygous for ’six’ mutation with more sugar content (5-1 1%) compared to field corn and contains phytoglycogen, a water soluble polysaccharide giving creamy texture to kernels..........